THE EFFECT OF AUGMENTED REALITY-BASED GEOGRAPHY LEARNING MODELS ON HIGH SCHOOL STUDENTS' LEARNING OUTCOMES - Anggara, Irma Murti Kusuma; Sukardjo, Moch; Solihatin, Etin (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the impact of augmented reality (AR)-based learning models on the academic achievement of high school students in geography education. As technological advancements continue to influence educational practices, AR offers an innovative approach to enhance students’ understanding of complex geographical concepts through immersive and interactive experiences. This research employs a quasi-experimental design involving two groups: an experimental group taught using AR-based methods and a control group receiving traditional instruction. Data collection includes pre-tests, post-tests, and student engagement questionnaires to assess learning outcomes and motivation levels. The results demonstrate a significant increase in the post-test scores of students taught with AR models compared to those taught through conventional methods, indicating an improvement in spatial understanding and retention of geographical knowledge. Students in the AR group exhibit higher motivation and active participation during lessons, which correlate with their academic performance. These findings suggest that integrating AR into geography instruction can effectively enhance learning outcomes. The study emphasizes the importance of incorporating emerging technologies into the curriculum to foster interactive and meaningful learning experiences that align with 21st-century skills. Overall, AR-based learning models present a promising pedagogical approach to improve learning outcomes and engagement in geography education at the secondary level.